2011
DOI: 10.1007/s10811-011-9652-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of an expression system using the heat shock protein 70 promoter in the red macroalga, Porphyra tenera

Abstract: Porphyra is a commercially valuable source of food and drugs, and represents an important model organism for algal research. However, genetic research on P. tenera has been limited due to lack of a heterologous gene expression system. In the present study, we isolated a native promoter, the PtHSP70 promoter, for efficient expression of foreign genes in this organism. This promoter lies approximately 1 kb upstream of the coding sequence for Heat Shock Protein 70 (HSP70) and was isolated using adapter-mediated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Thus, it is possible that the PyGUS gene could be commonly functional in red algae as a reporter of the gene expression. Indeed, applicability of the PyGUS gene in P. tenera has recently been confirmed by another laboratory (Son et al, 2011). The applicability of the P. yezoensis transient gene expression system was examined using the PyGUS and sGFP(S65T) reporter genes under the direction of the PyAct1 promoter in the red macroalgae listed in Table 2.…”
Section: Application Of Pygus and Sgfp(s65t) Reporter Systems In Othementioning
confidence: 91%
“…Thus, it is possible that the PyGUS gene could be commonly functional in red algae as a reporter of the gene expression. Indeed, applicability of the PyGUS gene in P. tenera has recently been confirmed by another laboratory (Son et al, 2011). The applicability of the P. yezoensis transient gene expression system was examined using the PyGUS and sGFP(S65T) reporter genes under the direction of the PyAct1 promoter in the red macroalgae listed in Table 2.…”
Section: Application Of Pygus and Sgfp(s65t) Reporter Systems In Othementioning
confidence: 91%
“…7 In addition, the promoter region of the HSP70 gene derived from P. tenera (PtHSP70 promoter) was shown to be active in P. yezoensis cells. 8 However, it remains to be determined whether the PtHSP70 promoter is available as a heterologous promoter in other Bangiophycean algal cells.…”
Section: The Hsp70 Promoter From P Tenera Functions As a Heterologoumentioning
confidence: 99%
“…In addition to our previous report on some heterologously employable promoters in Bangiophycean algae, 7,8 here we evaluate the P. tenera HSP70 promoter as an additional candidate for the heterologous promoter in red algal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, PyGUS and sGFP(S65T) genes act synergistically with the PyAct1 promoter as a heterologous promoter for transient transformation in Bangiophycean algae. Recently, the same synergistic effect was found in P. tenera; that is, Son et al [85] clearly indicated that the heat shock protein 70 (PtHSP70) promoter from P. tenera can activate the PyGUS gene in gametophytic cells of this alga. Moreover, the PtHSP70-PyGUS gene was expressed in P. yezoensis, P. okamurae, P. psedolinearis and B. fuscopurpurea [85,87].…”
Section: Applicability Of the P Yezoensis Transient Transformation Smentioning
confidence: 61%
“…EST analysis of P. haitanensis revealed that the GC content of the ORFs in this alga was as high as that in P. yezoensis, and analysis of the GAPDH gene from a Florideophycean alga Chondrus crispus showed a high GC content (approximately 60%) in the coding region [83,84], which is consistent with the codon preference in P. yezoensis. Since efficient expression of the GAPDH-PyGUS gene has recently been confirmed in P. tenera [85], the applicability of the P. yezoensis transient gene expression system in other red seaweeds is expected. Indeed, using the PyGUS and sGFP(S65T) reporter genes under the direction of the PyAct1 promoter, efficient expression of PyGUS and sGFP(S65T) genes was observed in Bangiophyceae including P. tenera, P. okamurae, P. psedolinearis and Bangia fuscopurpurea, although the expression efficiency varied among species [86].…”
Section: Applicability Of the P Yezoensis Transient Transformation Smentioning
confidence: 99%